THE PREVALENCE RATE OF ANTIBIOTIC RESISTANCE OF HELICOBACTER PYLORI AMONG CHILDREN: A SYSTEMATIC REVIEW: Pharmaceutical Science-Medicine - AHMED ASHI, MOHAMMED; SAEED ALZAHRANI, ANAS HASSAN; SAAD SAFAR ALGHAMDI, ABDULLAH; MAHMOUD MOHAMMED ALJOHANI, MARWAN; MOUSSA MAIMSH, OMER; WADEE ALHALABI, MOHAMMED (International Journal of Life Science and Pharma Research, 2019)
The lack of information regarding antibiotic susceptibility and H. pylori resistance in children is considered a major obstacle for H. pylori eradication. This review is aimed at collecting a comprehensive information about antibiotic resistance of H. pylori in children, to increase awareness about this population group. An electronic MEDLINE search was conducted using keywords with filter of “human studies”. The studies were screened for eligibility criteria such as studied population of children, the use of three or more antibiotics treatment, and the reporting antibiotic primary resistance for H. pylori as the outcomes of the study. The full texts of the eligible articles were retrieved and the secondary exclusion was done based on the full text reading by two independent evaluators from 2000-2018. The electronic search of the literature resulted in 98 studies. After exclusion of irrelevant, duplicated and review studies, 11 studies which met the inclusion criteria were selected. Included studies aimed to determine, from the best available evidence, the prevalence of antibiotics resistance towards H. pylori pathogen. The resistance rate of H. pylori to metronidazole ranged from 75.20% to 10.1%, while resistant rate for clarithromycin ranged from 84.9% to 11.9%, resistance rate for rifampicin ranged from 13.3% to 0.9%, for furazolidone it was 0.06%, and resistance rate for amoxicillin was 0.5% -3.9%. The highest resistance rate of H. pylori in children was reported for azithromycin followed by clarithromycin and metronidazole, while it was low for moxifloxacin, rifampicin, furazolidone, and very low for amoxicillin